1999
DOI: 10.1034/j.1399-3011.1999.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Spot synthesis: observations and optimizations

Abstract: Positionally addressable syntheses of peptides on continuous cellulose membranes (spot synthesis) have often been reported in detail, but important questions dealing with synthesis quality, reproducibility and subsequent binding assays have largely been under-emphasized. In this report we have investigated some of these problems. The most important results were: (i) the signal intensity of ligate binding to cellulose-bound peptides and the affinity of the corresponding soluble peptides show good correlation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 43 publications
(75 reference statements)
3
116
0
1
Order By: Relevance
“…In enzymatic reactions or protein binding studies it is often observed that the periphery of the peptide spot has more signal intensity than the center ("ring spot effect"). This effect can be due to the high density of peptides in the central part of the spot and then it can be resolved by downscaling the peptide synthesis 22 . For further trouble shooting of peptide synthesis the machine handbook and company service should be consulted.…”
Section: Discussionmentioning
confidence: 99%
“…In enzymatic reactions or protein binding studies it is often observed that the periphery of the peptide spot has more signal intensity than the center ("ring spot effect"). This effect can be due to the high density of peptides in the central part of the spot and then it can be resolved by downscaling the peptide synthesis 22 . For further trouble shooting of peptide synthesis the machine handbook and company service should be consulted.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of reliability of SPOT technology have been described by several authors [18][19][20] . Since purity and quantity of the peptides synthesized on cellulose may vary, all results achieved using this method need to be confirmed with peptides produced by conventional solid-phase peptide synthesis on resin.…”
Section: Experimental Designmentioning
confidence: 99%
“…The quality of SPOT-synthesized peptides has been investigated by several groups. Takahashi and co-workers [60] reported peptide purity higher than 92%, while Kramer and co-workers [61] reported lower purities. An extended HPLC analysis showed that purities of SPOT-synthesized short peptides of up to 15 amino acids are similar to those synthesized by solid-phase methods in reactors [62].…”
Section: Qualitative Explorative Investigations and Quantitative Analmentioning
confidence: 99%